Non-invasive CMR-Based Quantification of Myocardial Power and Efficiency Under Stress and Ischemic Conditions in Landrace Pigs - Faragli, Alessandro; Alogna, Alessio; Lee, Chong Bin; Zhu, Miry; Ghorbani, Niky; Lo Muzio, Francesco Paolo; Schnackenburg, Bernhard; Stehning, Christian; Kuehne, Titus; Post, Heiner; Goubergrits, Leonid; Nagel, Eike; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Myocardial efficiency should be maintained stable under light-to-moderate stress conditions, but ischemia puts the myocardium at risk for impaired functionality. Additionally, the measurement of such efficiency typically requires invasive heart catheterization and exposure to ionizing radiation. In this work, we aimed to non-invasively assess myocardial power and the resulting efficiency during pharmacological stress testing and ischemia induction. Methods: In a cohort of n=10 healthy Landrace pigs, dobutamine stress testing was performed, followed by verapamil-induced ischemia alongside to cardiac magnetic resonance (CMR) imaging. External myocardial power, internal myocardial power and myocardial efficiency were assessed non-invasively using geometrical and functional parameters from CMR volumetric as well as blood flow and pressures measurements. Results: External myocardial power significantly increased under dobutamine stress (2.3 [1.6-3.1] W/m2 vs. 1.3 [1.1-1.6] W/m2, p=0.005) and significantly decreased under verapamil-induced ischemia (0.8 [0.5-0.9] W/m2, p=0.005). Internal myocardial power (baseline: 5.9 [4.6-8.5] W/m2) was not affected by dobutamine (7.5 [6.9-9.0] W/m2, p=0.241) nor verapamil (5.8 [4.7-8.8] W/m2, p=0.878). Myocardial efficiency did not change from baseline to dobutamine (21 [15-27] % vs. 31 [20-44] %, p=0.059) but decreased significantly during verapamil-induced ischemia (10 [8-13] %, p=0.005). Conclusion: In healthy Landrace pigs, dobutamine stress increased external myocardial power whereas myocardial efficiency maintained stable. On the contrary, verapamil-induced ischemia substantially decreased external myocardial power and myocardial efficiency. Non-invasive CMR was able to quantify these efficiency losses and might be useful for future clinical studies evaluating the effects of therapeutic interventions on myocardial energetics.